OP99 Participatory Approaches Used In Research And Development Of Medical Devices: A Comparison Of Focus groups, Interviews And Surveys. (23rd December 2022) - Woudstra, Kas; Tummers, Marcia; Klijn, Catharina; Sondag, Lotte; Schreuder, Floris; Reuzel, Rob; Rovers, Maroeska
Abstract : Introduction: Multi-stakeholder engagement in the development and evaluation of medical devices is crucial for aligning devices with stakeholders' views, needs, and values. Focus groups, interviews, and surveys are often used to involve stakeholders, but these methods have rarely been compared to analyse their relative merits. Therefore, we systematically compared these three methods in terms of themes, interaction, and feasibility. Methods: The methods were compared in a case-study on surgery with a new endoscopic device for patients with intracerebral haemorrhage. We asked patients, relatives, healthcare professionals and decision-makers about their perspective on this device, and about their perceived quality of hospital care. We conducted the focus groups and interviews in one explorative and one interactive round. The comparison was made in terms of number and content of themes, who and how participants interact, and in terms of hours that needed to be worked by researchers to apply a method. Results: We enrolled 18 participants in the focus groups, 17 in the interviews and 43 in the survey. Focus groups generated 31 and 19 themes, and interviews 58 and 40 themes in the explorative and interactive round. Surveys generated 42 themes. Interviews produced various themes about the device that did not occur in the other methods. In the two rounds of the focus group, 13 and 42 percent of the interactions were directly between participants. In interview round one, 98 percent of the interactions were between the interviewer and participant, whereas 80 percent of the interactions in round two were discussions of other participants' opinions. In focus groups participants were inclined to emphasise agreement, whereas the interviews generated more in-depth discussions. Interviews took three times as many hours as the focus groups and survey. Conclusions: Methods for multi-stakeholder involvement in device development vary considerably. These methodological differences should be taken into account when selecting a method for engaging stakeholders in the early stages of the lifecycle of a medical device.